(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
The health-care industry is only one of several that has benefited from the revolutionary technology known as artificial intelligence (AI). AI might greatly enhance pharmaceutical practice by better-managing medications and patient care. Several AI applications in pharmacy practice are examined in this study. Using AI technology, chemists are equipped with methods and tools that enable them to make clinical judgments based on reliable evidence. Pharmacists can now analyze vast amounts of patient data, such as medical records, laboratory results, and medication profiles, with the help of AI algorithms and machine learning. This allows them to better assess the safety and effectiveness of medications, identify possible drug-drug interactions (DDIs), and make recommendations based on patient needs. Predicting and detecting adverse drug events, automating dispensing processes in community pharmacies, optimizing medication dosages, detecting DDIs, improving adherence through smart technologies, detecting and preventing medication errors, providing medication therapy management services, and supporting telemedicine initiatives are all possible with the help of specific AI models. Integrating AI into clinical practice allows health-care providers to enhance patient care through personalized decision-making. Various health-care services offered to a single patient may work together more effectively with the help of AI. When it comes to medication, AI could help patients remember to take their medication at the right times, educate them on the importance of taking their medication as prescribed, and increase the likelihood that they will take their medication as prescribed. AI could also help patients find the most affordable health-care options, improve their communication with health-care providers, optimize their health monitoring with wearable devices, offer guidance on healthy lifestyle choices every day, and even incorporate exercise and diet into their treatment plans.